Effect of sex and RYR1 gene mutation on the muscle proteomic profile and main physiological biomarkers in pigs at slaughter. (July 2018) - Oliván, Mamen; González, Joel; Bassols, Anna; Díaz, Fernando; Carreras, Ricard; Mainau, Eva; Arroyo, Laura; Peña, Raquel; Potes, Yaiza; Coto-Montes, Ana; Hollung, Kristin; Velarde, Antonio
Abstract: Gender and RYR1 gene mutation might have an effect on the muscle metabolic characteristics and on the animal's stress at slaughter, which could influence the process of muscle-to-meat conversion. Forty-eight pigs were distributed in a design including two factors: sex (male/female) and RYR1 genotype (NN/Nn). At slaughter, physiological blood biomarkers and muscle proteome were analyzed and carcass and meat quality traits were registered. Females had higher serum levels of glucose, urea, C-reactive protein "CRP", Pig-MAP and glutation-peroxidase "GPx" and lower levels of lactate, showed faster muscle pH decline and higher meat exudation. RYR1 mutation increased serum creatinine, creatine kinase and CRP and decreased GPx. The proteomic study highlighted significant effects of gender and RYR1 genotype on proteins related to fibre composition, antioxidant defense and post mortem glycolytic pathway, which correlate to differences of meat quality. This study provides interesting information on muscle biomarkers of the ultimate meat quality that are modulated by the animal's individual susceptibility to stress at slaughter.